STUDI DESKRIPTIF TENTANG FAKTOR RESIKO YANG MEMPENGARUHI KEJADIAN DIARE DI POSYAN DUBALITA DESA DARSONO RT 01 RW 02 DI WILAYAH KERJA PUSKESMAS ARJASA KABUPATEN JEMBER - Ahmad Efrizal Ammrullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2014)
Diarrhea is still a serious health problem and is faced by many countries, especially tropical, sub-tropical and developing countries. In a country like this the incidence of diarrhea is still quite high and often leads to death. Factors that influence the occurrence of diarrhea include: knowledge, attitudes, behavior, socioeconomic, environmental health, workplace, and sufferers themselves. The general purpose of this study is to identify risk factors that influence the occurrence of diarrhea, the specific goal is to identify the influence of the level of patient's knowledge about diarrheal diseases, attitudes and behavior of sufferers towards diarrheal disease. The design of this research is non-experimental descriptive type, the approach is cross sectional, ie the data is taken once and carried out in July 2012 at the Posyandu toddler in Darsono Village RT 02 RW 01 Arjasa District. The study sample of 20 people with diarrhea. Analysis of research data uses the One Sample Descriptive Chi-square statistical test with an error rate of 5% or a significance level of 95%. The results showed there was a significant influence between knowledge, attitudes, and behavior of sufferers on the incidence of diarrhea. The conclusion of the research is Ha> x2 table. Continued and continuous research is still needed to get a more real and complex picture of the risk factors that influence diarrhea, because there are many other risk factors that have not been studied due to various limitations. Continuous prevention efforts are needed to reduce the incidence of diarrhea in our society in order to achieve optimal health.